Analisis Performa Take Off Engine CFM56-7B Pada Thrust Tipe 26300 Lb - Sri Mulyani; Rudi Setiawan (Prosiding Seminar Nasional Sains Teknologi dan Inovasi Indonesia (SENASTINDO), 2021)
In some cases, if the engine performance descended, it could not be mantained as the standard perfomance requirements. According to CFM's engine manual, this case might be solved by down grading the engine configuration (TR) so that the engine still could be operated however it's performance was lower than earlier configuration. In this Final Assignment, the author discussed about comparison Take-Off performance of CFM56-7B engine between Thrust Rating configuration 26300 lbs. The performance calculation could be known by processing Test Cell Result data by the formula of Engine Shop Manual - 003. The purposes are to find the verification of both thrust rating configuration. The calculation of the take-off performance of the CFM56-7B engine with a 26300 lb thrust rating configuration based on the formula from the Engine Shop Manual-003 Engine Acceptance Test is a 26300 lb thrust rating configuration producing a thrust of 26920 lb. The SFC value obtained for the thrust rating is 0.3885 with an SFC margin of -5.3% and 0.382. The EGT generated by the engine is 905.9 C with an EGT margin of 17.1